IMPLEMENTASI METODE PROTOTYPE PADA SISTEM INFORMASI HASIL PANEN DAN TRANSAKSI AGROWISATA WANAYASA PURWAKARTA BERBASIS WEB DENGAN NOTIFIKASI EMAIL - Rafi Al-Faathir Koeswidayanto; Mochamad Adhari Adiguna (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Agriculture has a very important role in the process of human survival. In Indonesia, most of the population or people work in agriculture. This study aims to facilitate landowners and agro-tourism farmers in wanayasa purwakarta in processing and obtaining information about crop yields and transactions. Data obtained from direct observation of the object of research. The data is processed using the Prototype method. This research is the author's innovation with the hope of making it easier for agro-tourism farmers to process harvest data and transactions so that they are faster, more precise, and tidy in managing data, and can also help owners of agro-tourism land in Wanayasa Purwakarta in getting information about harvests and transactions with email notifications which makes land owners know if there is new harvest data and transactions without opening a website, and can be accessed anywhere without the need to visit the farmer concerned. The author designed a web-based information system for harvest data and transactions using the support software Visual Studio Code.